Zinc Triggers Microglial Activation - Tiina M. Kauppinen; Youichirou Higashi; Sang Won Suh; Carole Escartin; Kazuki Nagasawa; Raymond A. Swanson (2008)
Microglia are resident immune cells of the CNS. When stimulated by infection, tissue injury, or other signals, microglia assume an activated, “ameboid” morphology and release matrix metalloproteinases, reactive oxygen species, and other proinflammatory factors. This innate immune response augments host defenses, but it can also contribute to neuronal death. Zinc is released by neurons under several conditions in which microglial activation occurs, and zinc chelators can reduce neuronal death in animal models of cerebral ischemia and neurodegenerative disorders. Here, we show that zinc directly triggers microglial activation. Microglia transfected with a nuclear factor-κB (NF-κB) reporter gene showed a severalfold increase in NF-κB activity in response to 30 μ m zinc. Cultured mouse microglia exposed to 15–30 μ m zinc increased nitric oxide production, increased F4/80 expression, altered cytokine expression, and assumed the activated morphology. Zinc-induced microglial activation was blocked by inhibiting NADPH oxidase, poly(ADP-ribose) polymerase-1 (PARP-1), or NF-κB activation. Zinc injected directly into mouse brain induced microglial activation in wild-type mice, but not in mice genetically lacking PARP-1 or NADPH oxidase activity. Endogenous zinc release, induced by cerebral ischemia–reperfusion, likewise induced a robust microglial reaction, and this reaction was suppressed by the zinc chelator CaEDTA. Together, these results suggest that extracellular zinc triggers microglial activation through the sequential activation of NADPH oxidase, PARP-1, and NF-κB. These findings identify a novel trigger for microglial activation and a previously unrecognized mechanism by which zinc may contribute to neurological disorders.